Are you a spontaneous traveler? Effect of sensation seeking on tourist planfulness in the mobile era - Li, Qiuyun; Xu, Hong; Hu, Yubei (Frontiers in Psychology, 2022)
Drawn upon optimum stimulation level theory, and in view of the impact of mobile terminal usage on tourist decision making, the present study aims to investigate how personality (i.e., sensation seeking) influences tourist trip planning behavior (i.e., tourist planfulness) in the mobile era. A sample of 344 respondents in China completed measures of sensation seeking, travel risk perception, smartphone usage, as well as tourist planfulness. Results indicated that sensation seeking was negatively associated with tourist planfulness and travel risk perception partially mediated this association. Besides, both the direct effect of sensation seeking on tourist planfulness and the indirect effect of travel risk perception were moderated by smartphone usage, in that these effects were stronger for tourists with a high-level of smartphone usage than those with low-level smartphone usage. This study can significantly advance existing research on tourist behavior from the perspective of personality and reconfiguring our traditional understanding on tourist decision-making in the mobile era. Our study may also provide indicative support for theoretical perspective that information technology is changing customer behavior.